1997
DOI: 10.1111/j.1365-2249.1997.268-ce1165.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of CD45RO expression on circulating T lymphocytes of fetuses and newborn infants with pre-, peri- or early post-natal infections

Abstract: SUMMARYWe examined the expression of the CD45RO antigen, which characterizes the antigen primed/memory phenotype of T lymphocytes, as a marker for congenital infection in blood samples of newborns and fetuses. CD45RO expression on T cells was determined by triple-colour fluorescence flow cytometry. In total 537 blood samples of newborns and infants up to an age of 3 months and 89 fetal blood samples from gestational weeks 19-31 were analysed. Of the newborns and infants, 74 had a clinically, serologically and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 14 publications
3
18
2
Order By: Relevance
“…The lower number of CD45RO + T cells, compared with the full-term infant, likely contributes to the higher susceptibility to infection in these high-risk infants (43). Consistent with the lower proportion of memory/antigen-mature T cells, we found that at 42 d of age, the proportion of CD4 + CD45RA + cells in preterm infants was higher (33) than that in the literature for full-term infants (2,34,39,64). Contrary to that reported in adults (41) and fullterm infants, after 3 mon of age (39,64), ~10-20% of peripheral CD4 + and CD8 + cells in 42-d-old preterm infants did not express either of the CD45 isoforms (33).…”
Section: T-cell Development In the Preterm Infantsupporting
confidence: 80%
See 2 more Smart Citations
“…The lower number of CD45RO + T cells, compared with the full-term infant, likely contributes to the higher susceptibility to infection in these high-risk infants (43). Consistent with the lower proportion of memory/antigen-mature T cells, we found that at 42 d of age, the proportion of CD4 + CD45RA + cells in preterm infants was higher (33) than that in the literature for full-term infants (2,34,39,64). Contrary to that reported in adults (41) and fullterm infants, after 3 mon of age (39,64), ~10-20% of peripheral CD4 + and CD8 + cells in 42-d-old preterm infants did not express either of the CD45 isoforms (33).…”
Section: T-cell Development In the Preterm Infantsupporting
confidence: 80%
“…In the infant, the most frequently studied markers that delineate antigen naïve and mature T cells are the variant isoforms of CD45 (the common lymphocyte antigen), the CD45RA isoform (molecular weight 190,000-220,000), and the CD45RO isoform (molecular weight 180,000). CD45RO + T cells are believed to identify primed/memory (antigeneducated) cells and are derived from CD45RA + (naïve) cells after antigenic or mitogenic stimulation (34). The CD45RA antigen is first expressed late during intrathymic maturation and continues to be expressed by most circulating T cells in the infant (35)(36)(37).…”
Section: T-cell Development In the Term Neonatementioning
confidence: 99%
See 1 more Smart Citation
“…The expression of CD45 isoforms has been proposed as a potential marker for the diagnosis of perinatal infection and allograft rejection [20][21][22][23] . Hodge and co-workers 19 reported that all neonates with proven bacterial or viral infection had an increased number of either CD45RO+ cells (50%) or the dual expression cells CD45RA+/CD45RO+ (88%) at birth.…”
Section: Surface Markersmentioning
confidence: 99%
“…In contrast, in cases of viral infection, a high percentage of CD45RO+ cells persisted for at least 12-20 weeks 19 . Also, changes in the proportion of CD45RO+ and/or CD45RA+ cells in peripheral blood of adults have been observed in several chronic conditions, such as psoriasis 24 , rheumatoid arthritis 25 , atopic asthma 26 , human immunodeficiency virus infection 27,28 and renal allograft rejection 20,21,23 . Table 4 Correlation coefficient (Pearson correlation) among the study markers and gestational age (GA) at blood sampling in normal pregnant women (n = 89) The results of this study indicate that women with a fetal death had a higher percentage of CD45RO+ cells ('memory-like' T cells) and a lower proportion of CD45RA+ cells ('naive-like' T cells) in the CD4+ subset of lymphocytes than normal pregnant women.…”
Section: Surface Markersmentioning
confidence: 99%